2022
DOI: 10.3389/fonc.2022.1010976
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis-related lncRNAs: Combination of bulk and single-cell sequencing reveals immune landscape alteration and a novel prognosis stratification approach in lung adenocarcinoma

Abstract: Necroptosis, which is recently recognized as a form of programmed cell death, plays a critical role in cancer biology, including tumorigenesis and cancer immunology. It was recognized not only to defend against tumor progression by suppressing adaptive immune responses but also to promote tumorigenesis and cancer metastasis after recruiting inflammatory responses. Thus the crucial role of necrosis in tumorigenesis has attracted increasing attention. Due to the heterogeneity of the tumor immune microenvironment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The prognostic markers and the indications for prognosis in these studies are summarized in Table 2 . 36 , 44 , 45 , 47 49 , 55 89 DEGs and their combined prognostic model were the most common types of prognostic markers in these studies. For example, one study identified nine cancer-specific DEGs (CBFA2T3, CR2, SEL1L3, TM6SF1, TSPAN32, ITGA6, MAPK11, RASA3, and TLR6) and established a prognostic risk model in combination with clinical factors.…”
Section: The Prognostic Time Markers For Luadmentioning
confidence: 93%
See 1 more Smart Citation
“…The prognostic markers and the indications for prognosis in these studies are summarized in Table 2 . 36 , 44 , 45 , 47 49 , 55 89 DEGs and their combined prognostic model were the most common types of prognostic markers in these studies. For example, one study identified nine cancer-specific DEGs (CBFA2T3, CR2, SEL1L3, TM6SF1, TSPAN32, ITGA6, MAPK11, RASA3, and TLR6) and established a prognostic risk model in combination with clinical factors.…”
Section: The Prognostic Time Markers For Luadmentioning
confidence: 93%
“…The main findings from studies on TIME heterogeneity are summarized in Table 1 . 40 50 Early reports focused on the heterogeneity of key pathways or immune-related molecules. For example, genes of the γ-interferon (IFN-γ) signaling pathway, especially major histocompatibility complex (MHC) class II molecules, such as human leukocyte antigen (HLA), were found to be heterogeneously expressed and coregulated with other genes in single cancer cells across different LUAD nodules.…”
Section: The Heterogeneity Of Time In Luadmentioning
confidence: 99%